Bioanalytical method development and validation of bleomycin sulphate - Prashar, Yash; Rana, Harkaran Singh; Bais, Souravh (Creative Pharma Assent, 2017)
Bleomycin is an anti-neoplastic drug that has recently been used for the treatment of vascular anomalies. An expedient method was developed for the determination of plasma bleomycin levels using ion-paired reversed phase high performance liquid chromatography (HPLC). The concentration was found to be proportional to the area and the response of the detector was determined to be linear over the range of 1-6 µg/ml for both Bleomycin A1 and Bleomycin B2. Recovery was approximately 100%. This method provides a simple and rapid way of determining the levels of bleomycin A2 and B2 in human and rat plasma